Notte e dì (1984): una sperimentazione collettiva contemporanea a Viaggio in Italia - Milozzi, Adele (Rivista di studi di fotografia. Journal of Studies in Photography, 2019)
This essay offers the first sustained analysis and contextualization of Notte e dì, a photographic book on the National festival of the Italian Communist Party that Luigi Ghirri co-curated in 1984 in tandem with Viaggio in Italia, generally acknowledged as the cornerstone of the new “Italian school” of landscape photography. Involving five of the twenty photographers who had participated in the sister project few months earlier, Notte e dì shows aspects of consistency in terms of montage and graphic layout, while at the same time experimenting in uncommon ways with the text/image format, in tune with similar trends in contemporary literature, Visual poetry, and Conceptual Art.